Unpacking Social Capital for Growth and Development of Islamic Boarding School - Mochamad Nasichin Al Muiz; Syamsul Kurniawan; Muhammad Miftah; Feny Nida Fitriyani (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This article describes and analyzes the significance of social capital for the growth and development of the Integrated Islamic Boarding School Al Kamal in Blitar, East Java. It is the result of qualitative research aimed at illustrating, revealing, and explaining the importance of social capital for the Integrated Islamic Boarding School Al Kamal in Blitar, East Java. Data were collected through observation, in-depth interviews, and documentation, following John W. Creswell's qualitative research procedures. The data analysis technique used was interactive analysis, following the procedures of Matthew B. Miles, A.M. Huberman, and Saldana. Based on the research findings, it can be concluded that the presence of pesantren (Islamic boarding schools) is closely related to the role of social capital. Besides serving as educational and religious institutions, pesantren also play a crucial role as social institutions within the community. Social capital has become a vehicle for their growth and development. This trend is evident in the Integrated Islamic Boarding School Al Kamal in Blitar, East Java, where its growth and development are intricately connected to the social capital it has built and possesses. The types of social capital developed by the pesantren include bonding social capital, bridging social capital, and linking social capital.